Polymer-surfactant complexes effect on the flow in microchannels: An experimental approach - Fiona Ling, Wang Ming; Heidarinik, Somaye; Abdulbari, Hayder A. (Taylor & Francis, 2020)
Over the past few decades, experimental investigations have confirmed that it is not possible to enhance the flow in microfluidics channels due to its laminar flow nature. Reducing the scale of the carrying conduit (e.g. a microchannel) will enable the fluid properties, such as the viscosity and surface tension, to dominate and change the flow behavior. Most of the experimental efforts in this field focus on modifying the inner surfaces of the microchannels by controlling its hydrophobicity or hydrophilicity. The effect of active flow enhancement additives on the liquid flow in a microchannel is not addressed previously. The present work investigates the effect of two different types of viscoelastic additives, an anionic polymer (xanthan gum, XG) and a cationic surfactant (benzethonium chloride, BC), and their complexes on flow behavior in a 100 × 100 µm square microchannel. The effects of the additive concentrations and solution flow rates were investigated. The rheological and morphological properties of the solutions were tested using rheometer and cryo Transmission Electron Microscopy (cryo-TEM) techniques. The experimental results showed that the individual additives and their complexes can act as effective flow enhancement agents in a microchannel flow system. A maximum flow enhancement performance of 66% was achieved with the 300 ppm BC and 1000 ppm XG complex. It is believed that the interferences of the soluble additives in the microflow layers will be controlled by the aggregate size, which will result in different drag reduction behaviors.